Mechanical design aspects of a tri-axial accelerometer - Hatt, Joseph M. (Cranfield University, 2004)
This work describes the development of computer models for the design of a novel three-axis silicon accelerometer with thin-film PZT piezo-electric sensing. Theoretical and finite element methods are used to predict the resonant frequencies, resonant mode shapes, and charge sensitivity of the accelerometers. The strengths of each analytical method are used to allow the identification of trends in geometrical affects, and to optimise the design with respect to specification objectives for a commercial device. The theoretical models have been developed and refined in conjunction with practical fabrication trials. This has allowed the material properties to be derived, specific to the thin-film deposition method used, and incorporated onto the models. The practical fabrication process has raised a number of unforeseen issues, and these have led to changes from the original design. These changes have been analysed with the theoretical models, and revised performance predictions produced. The practical findings are consistent with the revised predictions, and achieve close to the desired performance specification.